19F NMR as a tool in chemical biology - Gimenez, Diana; Phelan, Aoife; Murphy, Cormac D.; Cobb, Steven L. (Beilstein Journal of Organic Chemistry, 2021)
We previously reviewed the use of 19F NMR in the broad field of chemical biology [Cobb, S. L.; Murphy, C. D. J. Fluorine Chem. 2009, 130, 132–140] and present here a summary of the literature from the last decade that has the technique as the central method of analysis. The topics covered include the synthesis of new fluorinated probes and their incorporation into macromolecules, the application of 19F NMR to monitor protein–protein interactions, protein–ligand interactions, physiologically relevant ions and in the structural analysis of proteins and nucleic acids. The continued relevance of the technique to investigate biosynthesis and biodegradation of fluorinated organic compounds is also described.
Keywords: biotransformation; chemical biology; fluorine; 19F NMR; probes; protein structure

(untitled) - O’Hagan, D.; Deng, H. (Chem. Rev., 2015)

(untitled) - Wu, L.; Maglangit, F.; Deng, H. (Curr. Opin. Chem. Biol., 2020)

(untitled) - Murphy, C. D. (Appl. Microbiol. Biotechnol., 2016)

(untitled) - Cobb, S. L.; Murphy, C. D. (J. Fluorine Chem., 2009)

(untitled) - Wang, J.; Xie, J.; Schultz, P. G. (J. Am. Chem. Soc., 2006)

(untitled) - Cotton, G. J.; Muir, T. W. (Chem. Biol., 1999)

(untitled) - Link, A. J.; Mock, M. L.; Tirrell, D. A. (Curr. Opin. Biotechnol., 2003)

(untitled) - Frieden, C.; Hoeltzli, S. D.; Bann, J. G. (Methods Enzymol., 2004)

(untitled) - Marsh, E. N. G.; Suzuki, Y. (ACS Chem. Biol., 2014)

(untitled) - Wang, L.; Brock, A.; Herberich, B.; Schultz, P. G. (Science, 2001)

(untitled) - Mills, J. H.; Lee, H. S.; Liu, C. C.; Wang, J.; Schultz, P. G. (ChemBioChem, 2009)

(untitled) - Young, T. S.; Ahmad, I.; Yin, J. A.; Schultz, P. G. (J. Mol. Biol., 2010)

(untitled) - Loscha, K. V.; Herlt, A. J.; Qi, R.; Huber, T.; Ozawa, K.; Otting, G. (Angew. Chem., Int. Ed., 2012)

(untitled) - Singh-Blom, A.; Hughes, R. A.; Ellington, A. D. (J. Biotechnol., 2014)

(untitled) - Buer, B. C.; Levin, B. J.; Marsh, E. N. G. (J. Pept. Sci., 2013)

(untitled) - Tressler, C. M.; Zondlo, N. J. (Org. Lett., 2016)

(untitled) - Tressler, C. M.; Zondlo, N. J. (J. Org. Chem., 2014)

Modern Synthesis Processes and Reactivity of Fluorinated Compounds - Vukelić, S.; Moschner, J.; Huhmann, S.; Fernandes, R.; Berger, A. A.; Koksch, B. (Synthesis of Side Chain Fluorinated Amino Acids and Their Effects on the Properties of Peptides and Proteins, 2017)

(untitled) - Salwiczek, M.; Samsonov, S.; Vagt, T.; Nyakatura, E.; Fleige, E.; Numata, J.; Cölfen, H.; Pisabarro, M. T.; Koksch, B. (Chem. – Eur. J., 2009)

(untitled) - Tressler, C. M.; Zondlo, N. J. (Biochemistry, 2017)

(untitled) - Lim, D. S.; Lin, J.-H.; Welch, J. T. (Eur. J. Org. Chem., 2012)

(untitled) - Grigolato, L.; Brittain, W. D. G.; Hudson, A. S.; Czyzewska, M. M.; Cobb, S. L. (J. Fluorine Chem., 2018)

(untitled) - Loewen, M. C.; Klein-Seetharaman, J.; Getmanova, E. V.; Reeves, P. J.; Schwalbe, H.; Khorana, H. G. (Proc. Natl. Acad. Sci. U. S. A., 2001)

(untitled) - Kim, T. H.; Chung, K. Y.; Manglik, A.; Hansen, A. L.; Dror, R. O.; Mildorf, T. J.; Shaw, D. E.; Kobilka, B. K.; Prosser, R. S. (J. Am. Chem. Soc., 2013)

(untitled) - Kalbitzer, H. R.; Rohr, G.; Nowak, E.; Goody, R. S.; Kuhn, W.; Zimmermann, E. (NMR Biomed., 1992)

(untitled) - Thomas, M. R.; Boxer, S. G. (Biochemistry, 2001)

(untitled) - Hellmich, U. A.; Pfleger, N.; Glaubitz, C. (Photochem. Photobiol., 2009)

(untitled) - Ye, L.; Larda, S. T.; Frank Li, Y. F.; Manglik, A.; Prosser, R. S. (J. Biomol. NMR, 2015)

(untitled) - Manglik, A.; Kim, T. H.; Masureel, M.; Altenbach, C.; Yang, Z.; Hilger, D.; Lerch, M. T.; Kobilka, T. S.; Thian, F. S.; Hubbell, W. L.; Prosser, R. S.; Kobilka, B. K. (Cell, 2015)

(untitled) - Gimenez, D.; Mooney, C. A.; Dose, A.; Sandford, G.; Coxon, C. R.; Cobb, S. L. (Org. Biomol. Chem., 2017)

(untitled) - Hattori, Y.; Heidenreich, D.; Ono, Y.; Sugiki, T.; Yokoyama, K.-i.; Suzuki, E.-i.; Fujiwara, T.; Kojima, C. (J. Biomol. NMR, 2017)

(untitled) - Spokoyny, A. M.; Zou, Y.; Ling, J. J.; Yu, H.; Lin, Y.-S.; Pentelute, B. L. (J. Am. Chem. Soc., 2013)

Annual Reports on NMR Spectroscopy - Dahanayake, J. N.; Kasireddy, C.; Karnes, J. P.; Verma, R.; Steinert, R. M.; Hildebrandt, D.; Hull, O. A.; Ellis, J. M.; Mitchell-Koch, K. R. (Progress in Our Understanding of 19F Chemical Shifts, 2018)

(untitled) - Urick, A. K.; Calle, L. P.; Espinosa, J. F.; Hu, H.; Pomerantz, W. C. K. (ACS Chem. Biol., 2016)

(untitled) - Richards, K. L.; Rowe, M. L.; Hudson, P. B.; Williamson, R. A.; Howard, M. J. (Sci. Rep., 2016)

(untitled) - Liu, J. J.; Horst, R.; Katritch, V.; Stevens, R. C.; Wüthrich, K. (Science, 2012)

(untitled) - Stadmiller, S. S.; Aguilar, J. S.; Waudby, C. A.; Pielak, G. J. (Biophys. J., 2020)

(untitled) - Dalvit, C.; Fagerness, P. E.; Hadden, D. T. A.; Sarver, R. W.; Stockman, B. J. (J. Am. Chem. Soc., 2003)

(untitled) - Dalvit, C.; Ardini, E.; Flocco, M.; Fogliatto, G. P.; Mongelli, N.; Veronesi, M. (J. Am. Chem. Soc., 2003)

(untitled) - Tressler, C. M.; Zondlo, N. J. (ACS Chem. Biol., 2020)

(untitled) - Dalvit, C.; Vulpetti, A. (J. Med. Chem., 2019)

(untitled) - Dalvit, C.; Veronesi, M.; Vulpetti, A. (J. Biomol. NMR, 2020)

(untitled) - Rydzik, A. M.; Leung, I. K. H.; Thalhammer, A.; Kochan, G. T.; Claridge, T. D. W.; Schofield, C. J. (Chem. Commun., 2014)

(untitled) - Ojima, I. (J. Fluorine Chem., 2017)

(untitled) - Veronesi, M.; Giacomina, F.; Romeo, E.; Castellani, B.; Ottonello, G.; Lambruschini, C.; Garau, G.; Scarpelli, R.; Bandiera, T.; Piomelli, D.; Dalvit, C. (Anal. Biochem., 2016)

(untitled) - Veronesi, M.; Romeo, E.; Lambruschini, C.; Piomelli, D.; Bandiera, T.; Scarpelli, R.; Garau, G.; Dalvit, C. (ChemMedChem, 2014)

(untitled) - Hong, M.; Schmidt-Rohr, K. (Acc. Chem. Res., 2013)

(untitled) - Gerig, J. T. (Prog. Nucl. Magn. Reson. Spectrosc., 1994)

(untitled) - Danielson, M. A.; Falke, J. J. (Annu. Rev. Biophys. Biomol. Struct., 1996)

(untitled) - Bann, J. G.; Pinkner, J.; Hultgren, S. J.; Frieden, C. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Kitevski-LeBlanc, J. L.; Hoang, J.; Thach, W.; Larda, S. T.; Prosser, R. S. (Biochemistry, 2013)

(untitled) - Skalicky, J. J.; Mills, J. L.; Sharma, S.; Szyperski, T. (J. Am. Chem. Soc., 2001)

(untitled) - Li, H.; Frieden, C. (Biochemistry, 2007)

(untitled) - Baturin, S. J.; Okon, M.; McIntosh, L. P. (J. Biomol. NMR, 2011)

(untitled) - Evanics, F.; Bezsonova, I.; Marsh, J.; Kitevski, J. L.; Forman-Kay, J. D.; Prosser, R. S. (Biochemistry, 2006)

(untitled) - Evanics, F.; Kitevski, J. L.; Bezsonova, I.; Forman-Kay, J.; Prosser, R. S. (Biochim. Biophys. Acta, Gen. Subj., 2007)

(untitled) - Kitevski-LeBlanc, J. L.; Evanics, F.; Prosser, R. S. (J. Biomol. NMR, 2009)

(untitled) - Matei, E.; Gronenborn, A. M. (Angew. Chem., Int. Ed., 2016)

(untitled) - Wang, G.-F.; Li, C.; Pielak, G. J. (Protein Sci., 2010)

(untitled) - Wang, G.-F.; Li, C.; Pielak, G. J. (ChemBioChem, 2010)

(untitled) - Buer, B. C.; Chugh, J.; Al-Hashimi, H. M.; Marsh, E. N. G. (Biochemistry, 2010)

(untitled) - Suzuki, Y.; Brender, J. R.; Soper, M. T.; Krishnamoorthy, J.; Zhou, Y.; Ruotolo, B. T.; Kotov, N. A.; Ramamoorthy, A.; Marsh, E. N. G. (Biochemistry, 2013)

(untitled) - Larda, S. T.; Simonetti, K.; Al-Abdul-Wahid, M. S.; Sharpe, S.; Prosser, R. S. (J. Am. Chem. Soc., 2013)

(untitled) - Aramini, J. M.; Hamilton, K.; Ma, L.-C.; Swapna, G. V. T.; Leonard, P. G.; Ladbury, J. E.; Krug, R. M.; Montelione, G. T. (Structure, 2014)

(untitled) - Aramini, J. M.; Ma, L.-C.; Zhou, L.; Schauder, C. M.; Hamilton, K.; Amer, B. R.; Mack, T. R.; Lee, H.-W.; Ciccosanti, C. T.; Zhao, L.; Xiao, R.; Krug, R. M.; et al. (J. Biol. Chem., 2011)

(untitled) - Dobson, C. M. (Nature, 2003)

(untitled) - Yan, Y.; Wang, C. (J. Mol. Biol., 2006)

(untitled) - Mishra, R.; Geyer, M.; Winter, R. (ChemBioChem, 2009)

(untitled) - Suzuki, Y.; Brender, J. R.; Hartman, K.; Ramamoorthy, A.; Marsh, E. N. G. (Biochemistry, 2012)

(untitled) - Ma, B.; Nussinov, R. (J. Mol. Biol., 2012)

(untitled) - Kitevski-LeBlanc, J. L.; Evanics, F.; Scott Prosser, R. (J. Biomol. NMR, 2010)

(untitled) - Uversky, V. N. (Front. Phys., 2019)

(untitled) - Sciolino, N.; Burz, D. S.; Shekhtman, A. (Proteomics, 2019)

Methods in Enzymology - Cook, E. C.; Usher, G. A.; Showalter, S. A. (The Use of 13C Direct-Detect NMR to Characterize Flexible and Disordered Proteins, 2018)

(untitled) - Li, C.; Lutz, E. A.; Slade, K. M.; Ruf, R. A. S.; Wang, G.-F.; Pielak, G. J. (Biochemistry, 2009)

(untitled) - Zigoneanu, I. G.; Yang, Y. J.; Krois, A. S.; Haque, M. E.; Pielak, G. J. (Biochim. Biophys. Acta, Biomembr., 2012)

(untitled) - Zigoneanu, I. G.; Pielak, G. J. (Mol. Pharmaceutics, 2012)

(untitled) - Li, C.; Wang, G.-F.; Wang, Y.; Creager-Allen, R.; Lutz, E. A.; Scronce, H.; Slade, K. M.; Ruf, R. A. S.; Mehl, R. A.; Pielak, G. J. (J. Am. Chem. Soc., 2010)

(untitled) - Somlyay, M.; Ledolter, K.; Kitzler, M.; Sandford, G.; Cobb, S. L.; Konrat, R. (ChemBioChem, 2020)

(untitled) - Coller, H. A.; Grandori, C.; Tamayo, P.; Colbert, T.; Lander, E. S.; Eisenman, R. N.; Golub, T. R. (Proc. Natl. Acad. Sci. U. S. A., 2000)

(untitled) - Fieber, W.; Schneider, M. L.; Matt, T.; Kräutler, B.; Konrat, R.; Bister, K. (J. Mol. Biol., 2001)

(untitled) - Sanders, C. R.; Sönnichsen, F. (Magn. Reson. Chem., 2006)

(untitled) - Lacapère, J.-J.; Pebay-Peyroula, E.; Neumann, J.-M.; Etchebest, C. (Trends Biochem. Sci., 2007)

(untitled) - Pandey, A.; Shin, K.; Patterson, R. E.; Liu, X.-Q.; Rainey, J. K. (Biochem. Cell Biol., 2016)

(untitled) - Yu, H. (Proc. Natl. Acad. Sci. U. S. A., 1999)

(untitled) - Warschawski, D. E.; Arnold, A. A.; Beaugrand, M.; Gravel, A.; Chartrand, É.; Marcotte, I. (Biochim. Biophys. Acta, Biomembr., 2011)

(untitled) - Di Pietrantonio, C.; Pandey, A.; Gould, J.; Hasabnis, A.; Prosser, R. S. (Methods Enzymol., 2019)

(untitled) - Bondarenko, V.; Wells, M. M.; Chen, Q.; Singewald, K. C.; Saxena, S.; Xu, Y.; Tang, P. (ACS Chem. Biol., 2019)

(untitled) - Boeszoermenyi, A.; Ogórek, B.; Jain, A.; Arthanari, H.; Wagner, G. (J. Biomol. NMR, 2020)

(untitled) - Kreutz, C.; Kählig, H.; Konrat, R.; Micura, R. (J. Am. Chem. Soc., 2005)

(untitled) - Puffer, B.; Kreutz, C.; Rieder, U.; Ebert, M.-O.; Konrat, R.; Micura, R. (Nucleic Acids Res., 2009)

(untitled) - Graber, D.; Moroder, H.; Micura, R. (J. Am. Chem. Soc., 2008)

(untitled) - Fauster, K.; Kreutz, C.; Micura, R. (Angew. Chem., Int. Ed., 2012)

(untitled) - Rhodes, D.; Lipps, H. J. (Nucleic Acids Res., 2015)

(untitled) - Hirashima, K.; Seimiya, H. (Nucleic Acids Res., 2015)

(untitled) - Xu, Y.; Ishizuka, T.; Yang, J.; Ito, K.; Katada, H.; Komiyama, M.; Hayashi, T. (J. Biol. Chem., 2012)

(untitled) - Takahama, K.; Takada, A.; Tada, S.; Shimizu, M.; Sayama, K.; Kurokawa, R.; Oyoshi, T. (Chem. Biol., 2013)

(untitled) - Wang, C.; Zhao, L.; Lu, S. (Int. J. Biol. Sci., 2015)

(untitled) - Bao, H.-L.; Xu, Y. (Chem. Commun., 2020)

(untitled) - Ishizuka, T.; Bao, H. L.; Xu, Y. (Methods Mol. Biol. (N. Y., NY, U. S.), 2019)

(untitled) - Granqvist, L.; Virta, P. (J. Org. Chem., 2015)

(untitled) - Bao, H.-L.; Ishizuka, T.; Sakamoto, T.; Fujimoto, K.; Uechi, T.; Kenmochi, N.; Xu, Y. (Nucleic Acids Res., 2017)

(untitled) - Bao, H.-L.; Ishizuka, T.; Iwanami, A.; Oyoshi, T.; Xu, Y. (ChemistrySelect, 2017)

(untitled) - Bao, H.-L.; Liu, H.-s.; Xu, Y. (Nucleic Acids Res., 2019)

(untitled) - Amadio, J.; Gordon, K.; Murphy, C. D. (Appl. Environ. Microbiol., 2010)

(untitled) - Palmer-Brown, W.; de Melo Souza, P. L.; Murphy, C. D. (Environ. Sci. Pollut. Res., 2019)

(untitled) - Palmer-Brown, W.; Dunne, B.; Ortin, Y.; Fox, M. A.; Sandford, G.; Murphy, C. D. (Xenobiotica, 2017)

(untitled) - Pujol, E.; Blanco-Cabra, N.; Julián, E.; Leiva, R.; Torrents, E.; Vázquez, S. (Molecules, 2018)

(untitled) - Pertusati, F.; Ferla, S.; Bassetto, M.; Brancale, A.; Khandil, S.; Westwell, A. D.; McGuigan, C. (Eur. J. Med. Chem., 2019)

(untitled) - Saccomanno, M.; Hussain, S.; O’Connor, N. K.; Beier, P.; Somlyay, M.; Konrat, R.; Murphy, C. D. (Biodegradation, 2018)

(untitled) - Sanada, M.; Miyano, T.; Iwadare, S.; Williamson, J. M.; Arison, B. H.; Smith, J. L.; Douglas, A. W.; Liesch, J. M.; Inamine, E. (J. Antibiot., 1986)

(untitled) - Huang, S.; Ma, L.; Tong, M. H.; Yu, Y.; O'Hagan, D.; Deng, H. (Org. Biomol. Chem., 2014)

(untitled) - Ma, L.; Bartholome, A.; Tong, M. H.; Qin, Z.; Yu, Y.; Shepherd, T.; Kyeremeh, K.; Deng, H.; O'Hagan, D. (Chem. Sci., 2015)

(untitled) - Wu, L.; Tong, M. H.; Kyeremeh, K.; Deng, H. (Biomolecules, 2020)

(untitled) - Markakis, K.; Lowe, P. T.; Davison‐Gates, L.; O'Hagan, D.; Rosser, S. J.; Elfick, A. (ChemBioChem, 2020)

(untitled) - Waller, C. W.; Patrick, J. B.; Fulmor, W.; Meyer, W. E. (J. Am. Chem. Soc., 1957)

(untitled) - Morton, G. O.; Lancaster, J. E.; Van Lear, G. E.; Fulmor, W.; Meyer, W. E. (J. Am. Chem. Soc., 1969)

(untitled) - Zhu, X. M.; Hackl, S.; Thaker, M. N.; Kalan, L.; Weber, C.; Urgast, D. S.; Krupp, E. M.; Brewer, A.; Vanner, S.; Szawiola, A.; Yim, G.; Feldmann, J.; et al. (ChemBioChem, 2015)

(untitled) - Feng, X.; Bello, D.; Lowe, P. T.; Clark, J.; O'Hagan, D. (Chem. Sci., 2019)

(untitled) - Phister, T. G.; O'Sullivan, D. J.; McKay, L. L. (Appl. Environ. Microbiol., 2004)

(untitled) - O’Connor, N. K.; Hudson, A. S.; Cobb, S. L.; O’Neil, D.; Robertson, J.; Duncan, V.; Murphy, C. D. (Amino Acids, 2014)

(untitled) - O’Connor, N. K.; Rai, D. K.; Clark, B. R.; Murphy, C. D. (J. Fluorine Chem., 2012)

(untitled) - Moran, S.; Rai, D. K.; Clark, B. R.; Murphy, C. D. (Org. Biomol. Chem., 2009)

(untitled) - Piasecki, S. K.; Keatinge-Clay, A. T. (Synlett, 2012)

(untitled) - Yu, J.-X.; Kodibagkar, V. D.; Liu, L.; Zhang, Z.; Liu, L.; Magnusson, J.; Liu, Y. (Chem. Sci., 2013)

(untitled) - Matsushita, H.; Mizukami, S.; Mori, Y.; Sugihara, F.; Shirakawa, M.; Yoshioka, Y.; Kikuchi, K. (ChemBioChem, 2012)

(untitled) - Smith, G. A.; Hesketh, R. T.; Metcalfe, J. C.; Feeney, J.; Morris, P. G. (Proc. Natl. Acad. Sci. U. S. A., 1983)

(untitled) - Bar-Shir, A.; Gilad, A. A.; Chan, K. W. Y.; Liu, G.; van Zijl, P. C. M.; Bulte, J. W. M.; McMahon, M. T. (J. Am. Chem. Soc., 2013)

(untitled) - Bar-Shir, A.; Yadav, N. N.; Gilad, A. A.; van Zijl, P. C. M.; McMahon, M. T.; Bulte, J. W. M. (J. Am. Chem. Soc., 2015)

(untitled) - Sakamoto, T.; Hayakawa, H.; Fujimoto, K. (Chem. Lett., 2011)

(untitled) - Gan, H.; Oliver, A. G.; Smith, B. D. (Chem. Commun., 2013)

(untitled) - Ray, P. D.; Huang, B.-W.; Tsuji, Y. (Cell. Signalling, 2012)

(untitled) - Lippert, A. R.; Van de Bittner, G. C.; Chang, C. J. (Acc. Chem. Res., 2011)

(untitled) - Nonaka, H.; An, Q.; Sugihara, F.; Doura, T.; Tsuchiya, A.; Yoshioka, Y.; Sando, S. (Anal. Sci., 2015)

(untitled) - Bruemmer, K. J.; Merrikhihaghi, S.; Lollar, C. T.; Morris, S. N. S.; Bauer, J. H.; Lippert, A. R. (Chem. Commun., 2014)